The Impact of Preoperative Immune Modulating Nutrition on Outcomes in Patients Undergoing Surgery for Gastrointestinal Cancer: A Systematic Review and Meta-analysis - Adiamah, Alfred; Skořepa, Pavel; Weimann, Arved; Lobo, Dileep N (Annals of surgery, 2019)
OBJECTIVE: To define the influence of preoperative immune modulating nutrition (IMN) on postoperative outcomes in patients undergoing surgery for gastrointestinal cancer. BACKGROUND: Although studies have shown that perioperative IMN may reduce postoperative infectious complications, many of these have included patients with benign and malignant disease, and the optimal timing of such an intervention is not clear. METHODS: The Embase, Medline, and Cochrane databases were searched from 2000 to 2018, for prospective randomized controlled trials evaluating preoperative oral or enteral IMN in patients undergoing surgery for gastrointestinal cancer. The primary endpoint was the development of postoperative infectious complications. Secondary endpoints included postoperative noninfectious complications, length of stay, and up to 30-day mortality. The analysis was performed using RevMan v5.3 software. RESULTS: Sixteen studies reporting on 1387 patients (715 IMN group, 672 control group) were included. Six of the included studies reported on a mixed population of patients undergoing all gastrointestinal cancer surgery. Of the remaining, 4 investigated IMN in colorectal cancer surgery, 2 in pancreatic surgery, and another 2 in patients undergoing surgery for gastric cancer. There was 1 study each on liver and esophageal cancer. The formulation of nutrition used in all studies in the treated patients was Impact (Novartis/Nestlé), which contains ω-3 fatty acids, arginine, and nucleotides. Preoperative IMN in patients undergoing surgery for gastrointestinal cancer reduced infectious complications [odds ratio (OR) 0.52, 95% confidence interval (CI) 0.38-0.71, P < 0.0001, I = 16%, n = 1387] and length of hospital stay (weighted mean difference -1.57 days, 95% CI -2.48 to -0.66, P = 0.0007, I = 34%, n = 995) when compared with control (isocaloric isonitrogeneous feed or normal diet). It, however, did not affect noninfectious complications (OR 0.98, 95% CI 0.73-1.33, P = 0.91, I = 0%, n = 1303) or mortality (OR 0.55, 95% CI 0.18-1.68, P = 0.29, I = 0%, n = 955). CONCLUSION: Given the significant impact on infectious complications and a tendency to shorten length of stay, preoperative IMN should be encouraged in routine practice in patients undergoing surgery for gastrointestinal cancer.
Keywords: Postoperative Cognitive Complications; Immunologic Factors; imunologické faktory; pooperační kognitivní dysfunkce; enterální výživa; nutriční stav; předoperační péče; Digestive System Surgical Procedures; Nutritional Status; gastrointestinální nádory; chirurgie trávicího traktu; Preoperative Care; Humans; lidé; Gastrointestinal Neoplasms; Enteral Nutrition